Access to Higher Education: The Israeli Case - Ben-David, Iris; Iram, Yaakov (International Higher Education, 2014)
Israeli higher education has exhibited a high level of academic achievement. However, access to higher education is at the middle level compared with the OECDs and has presented a middle rate of improvement. Stratification is still evident, especially, for minority students and for students from low socio-economic strata. Equity issues for previous schooling levels nurture stratification in higher education. We argue that there is a need for a holistic equitable school policy reform.